Multi-mode synergistic antibacterial nano material as well as preparation method and application thereof
By loading copper nanoclusters on the surface of two-dimensional silene nanosheets, combining photothermal and chemical kinetic therapy, the limitations of two-dimensional silene in antibacterial treatment are solved, and efficient multi-mode synergistic antibacterial effects are achieved, enhancing the removal ability of drug-resistant bacteria and biofilms, and optimizing biocompatibility.
Patent Information
- Application Number
- CN202510548822.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-08-01
AI Technical Summary
Traditional two-dimensional silenes have problems such as limited photothermal effect, low catalytic activity, difficulty in removing biofilms and insufficient biosafety in antibacterial treatment, which limits their application in implant-related infection treatment.
By loading copper nanoclusters (CuNCs) on the surface of two-dimensional silene nanosheets, combining photothermal therapy (PTT) and chemokinetic therapy (CDT), enhancing catalytic activity and destroying bacterial biofilms, optimizing the biocompatibility of the material.
It improves the antibacterial effect, enhances the removal ability of drug-resistant bacteria and biofilms, reduces the biotoxicity of the material, expands the antibacterial mechanism of two-dimensional silenes, and realizes multi-modal collaborative sterilization.
Smart Images

Figure CN120393005A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technologies, and in particular, to a multi-modal collaborative antibacterial nanomaterial, a preparation method thereof, and an application thereof. Background Art
[0002] Implant-Associated Infections (IAIs) are one of the most common and challenging complications in orthopedic surgeries, seriously affecting the bone integration effect, leading to recurrence of infections, and increasing the surgical repair difficulty and medical burden of patients. Traditional antibiotic treatment strategies can achieve certain effects in the initial stage of antibacterial treatment. However, due to the abuse of antibiotics, drug-resistant bacteria (such as methicillin-resistant Staphylococcus aureus MRSA) have become a current clinical problem that is difficult to overcome. In addition, bacteria are prone to form biofilms on the surface of implants, and the bacteria therein can enter a dormant state (persister bacteria), which have extremely strong tolerance to antibiotics, making it difficult to eradicate the infection.
[0003] In recent years, Chemodynamic Therapy (CDT), as an antibiotic-free antibacterial strategy, has received extensive attention. CDT is mainly based on Fenton or Fenton-like catalytic reactions, using metal nanocatalysts (such as Fe 3+ , Cu 2+ ) to catalyze the generation of hydroxyl radicals (·OH) from hydrogen peroxide (H2O2) in the body, thereby killing bacteria. However, the catalytic efficiency of traditional iron-based CDT nanomaterials in the physiological environment is relatively low. Because Fe 3+ is prone to form stable complexes at pH>5, restricting the cyclic reaction kinetics of Fe 2+ / Fe 3+ , and limiting its practical application. In addition, although copper-based catalysts have higher catalytic activities, copper nanoclusters (Cu NCs) are prone to agglomeration in complex physiological environments, thereby reducing the catalytic efficiency.
[0004] As a new type of two-dimensional nanomaterial developed in recent years, two-dimensional silicene has attracted attention in the biomedical field due to its ultrathin layered structure, high specific surface area, and excellent optical and electronic properties. However, the main biological applications of traditional two-dimensional silicene mainly focus on photothermal therapy (PTT), that is, under near-infrared (NIR) light irradiation, the material can efficiently convert light energy into heat energy, thereby increasing the temperature in the local environment, denaturing bacterial proteins, and ultimately causing bacterial death. To a certain extent, this photothermal effect can inhibit bacterial growth, but the antibacterial effect of single photothermal therapy is limited. Especially in complex infection environments, heat-resistant strains may enhance their temperature tolerance through mechanisms such as the expression of heat shock proteins (HSPs), resulting in a decline in the treatment effect. Currently, pure two-dimensional silicene still has problems such as limited photothermal antibacterial effect, low catalytic activity, difficulty in removing biofilms, single antibacterial mechanism, and biosafety in antibacterial treatment, which limit its further application in clinical antibacterial treatment. Therefore, developing a two-dimensional nanomaterial with high catalytic activity, capable of enhancing the synergistic antibacterial ability of photothermal-catalysis, and having good biocompatibility at the same time is the key direction to improve the application value of two-dimensional materials in the field of infection treatment. Summary of the Invention
[0005] The object of the present invention is to provide a multi-mode synergistic antibacterial nanomaterial, its preparation method and application in view of the deficiencies in the prior art.
[0006] To achieve the above object, the technical solutions adopted by the present invention are as follows:
[0007] In the first aspect, a multi-mode synergistic antibacterial nanomaterial is provided, including two-dimensional silicene nanosheets and copper nanoclusters loaded on their surfaces.
[0008] In the second aspect, a preparation method of the above multi-mode synergistic antibacterial nanomaterial is provided, including the following steps:
[0009] Step 1, prepare high-quality two-dimensional silicene nanosheets by wet chemical exfoliation method;
[0010] Step 2, synthesize CuNCs by chemical reduction method;
[0011] Step 3, slowly add the Cu NCs dispersion to the two-dimensional silicene nanosheet suspension and ultrasonicate at room temperature to promote the uniform distribution of Cu NCs on the surface of the two-dimensional silicene nanosheets; continue to stir vigorously to ensure that Cu NCs are fully loaded onto the surface of the two-dimensional silicene nanosheets to form a stable Si@CuNSs composite material; centrifuge to remove unbound Cu NCs and wash repeatedly with deionized water to obtain the multi-mode synergistic antibacterial nanomaterial.
[0012] Furthermore, the specific method for preparing high-quality two-dimensional silicene nanosheets by wet chemical exfoliation is as follows: Under an argon protective atmosphere, weigh the CaSi2 precursor and iodine, disperse them in anhydrous acetonitrile at a molar ratio of 1:1, and stir at room temperature for 2 - 3 weeks to promote the formation of silicene; after the reaction is completed, use centrifugation to remove by-products and wash multiple times to improve the purity of the two-dimensional silicene nanosheets.
[0013] Furthermore, the specific method for synthesizing CuNCs by chemical reduction method is as follows: Dissolve CuSO4·5H2O in ultrapure water, add glutathione as a stabilizer, and adjust the solution pH to 4.0 - 5.0, and reduce Cu ions by chemical reduction to form CuNCs.
[0014] Furthermore, the concentration of CuSO4·5H2O is 0.5 - 0.8 mM; the concentration of glutathione is 5 - 7 mg / mL; the reducing agent used is NaBH4.
[0015] Furthermore, the preparation method of the two-dimensional silicene nanosheet suspension is as follows: Redisperse the two-dimensional silicene nanosheets prepared in step one in N-methylpyrrolidone solution, and ultrasonically treat it at 900 W for 8 - 12 hours under ice bath conditions to finally obtain a highly dispersible two-dimensional silicene nanosheet suspension.
[0016] Furthermore, the concentration of CuNCs in the Cu NCs dispersion is 5 - 10 mg / mL; the concentration of two-dimensional silicene nanosheets in the two-dimensional silicene nanosheet suspension is 10 - 15 mg / mL.
[0017] Furthermore, in the third step, the ultrasonic time is 1 - 3 hours, and the vigorous stirring time is 1 - 3 hours.
[0018] The third aspect is to provide the application of the above multi-mode synergistic antibacterial nanomaterials in the preparation of anti-bacterial infection drugs.
[0019] The present invention adopts the above technical solutions, and compared with the prior art, has the following technical effects:
[0020] In the Si@CuNSs composite material of the present invention, by loading copper nanoclusters (CuNCs) on the surface of two-dimensional silicene nanosheets, the catalytic activity of copper is enhanced by using the p-d orbital hybridization effect, and at the same time, photothermal therapy (PTT) and chemodynamic therapy (CDT) are combined to synergistically remove drug-resistant bacteria and biofilms, thereby overcoming the limitations of traditional two-dimensional silicene in antibacterial applications.
[0021] (1)Enhance the catalytic activity of two-dimensional silicene and improve the CDT efficiency: Traditional two-dimensional silicene mainly relies on the photothermal effect (PTT) in antibacterial applications. However, its chemical catalytic ability is weak, and it is difficult to efficiently catalyze H2O2 to generate free radicals (·OH), resulting in limited CDT effects. In this invention, by loading CuNCs on the surface of two-dimensional silicene, the redox cycle between Cu + / Cu 2+ is enhanced through p-d orbital hybridization effect, improving the decomposition efficiency of H2O2, thereby enhancing the ability of CDT to generate free radicals and enhancing the antibacterial effect.
[0022] (2)Destroy bacterial biofilms and improve the clearance rate of persister bacteria: Bacterial biofilms are a protective barrier composed of extracellular polymeric substances (EPS) such as polysaccharides, proteins, and nucleic acids, enabling bacteria to resist the attack of antibiotics and free radicals. Ordinary two-dimensional silicene is difficult to effectively penetrate and destroy biofilms, resulting in the difficulty of completely clearing persister bacteria. In this invention, by introducing CuNCs, the biofilm penetration ability of the material is enhanced, and combined with the synergistic effect of photothermal-CDT, the structure of bacterial biofilms is destroyed, and the clearance rate of persister bacteria is improved, thereby reducing the risk of infection recurrence.
[0023] (3)Expand the antibacterial mechanism of two-dimensional silicene and achieve multi-mode synergistic bactericidal effect: The antibacterial mechanism of traditional two-dimensional silicene mainly relies on the photothermal effect (PTT). However, some bacteria can enhance their heat resistance through the expression of heat shock proteins (HSPs), thereby reducing the antibacterial effect of PTT. In addition, a single free radical bactericidal method may lead to unstable CDT effects in the case of insufficient H2O2 concentration. This invention combines the photothermal-catalytic synergistic antibacterial strategy, uses the high temperature generated by PTT to damage the bacterial membrane, and at the same time enhances the catalytic activity of CuNCs to improve the CDT efficiency, achieving efficient clearance of drug-resistant bacteria.
[0024] (4)Optimize the biocompatibility of the material and reduce potential biotoxicity: Some metal catalysts are prone to release metal ions in the physiological environment, which may cause cytotoxicity or inflammatory reactions. In this invention, by optimizing the method of loading Cu NCs on two-dimensional silicene, the stability of CuNCs in the material is ensured, the release of free metal ions is reduced, thereby reducing biotoxicity. At the same time, silicene itself has good biocompatibility and will not cause immune rejection, improving its application value in biomedicine. Brief Description of the Drawings
[0025] Figure 1 Shows the characterization results of Si@CuNSs prepared in Example 1; among them, (a) is the transmission electron microscope image of Si@Cu NSs; (b) is the elemental distribution image of Si@CuNSs; (c) is the atomic force microscope image of Si@Cu NSs.
[0026] Figure 2 Calculation of the catalytic performance of Si@Cu NSs.
[0027] Figure 3 The detection results of the catalytic performance of Si@Cu NSs are shown; among them, (a) is the absorption spectrum of different materials in the wavelength range of 400 nm to 1200 nm; (b) is the absorption spectrum after the catalytic decomposition of methylene blue (MB) by different materials; (c) is the electron paramagnetic resonance (EPR) spectrum of different materials.
[0028] Figure 4 The test results of the antibacterial ability of Si@Cu NSs are shown; among them, (a) is the antibacterial detection of Si@Cu; (b) is the flow cytometry quantification of the antibacterial ability of Si@Cu; (c) is the TEM image of bacteria after different treatments.
[0029] Figure 5 The in vivo biosafety evaluation results of Si@Cu NSs are shown. Specific implementation mode
[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but it is not a limitation of the present invention. It should be noted that, without conflict, the embodiments in the present invention and the features in the embodiments can be combined with each other.
[0031] Example 1
[0032] This example provides a preparation method of a multi-mode synergistic antibacterial nanomaterial. The multi-mode synergistic antibacterial nanomaterial includes two-dimensional silicene nanosheets and copper nanoclusters loaded on their surfaces. The specific preparation method includes the following steps:
[0033] Step 1, under an argon (Ar) protective atmosphere, weigh 480 mg of CaSi2 precursor and 1270 mg of iodine, disperse them in 120 mL of anhydrous acetonitrile (CH3CN) according to a molar ratio of 1:1, and stir at room temperature for 2 weeks to promote the formation of silicene; after the reaction is completed, use centrifugal separation to remove by-products and wash multiple times to improve purity; subsequently, redisperse the obtained product in 50 mL of N-methylpyrrolidone (NMP) solution and ultrasonically treat it at 900 W for 12 hours under ice bath conditions to finally obtain a highly dispersed two-dimensional silicene nanosheet suspension (SiNSs).
[0034] Step 2, dissolve CuSO4·5H2O in 50 mL of ultrapure water (CuSO4 concentration 0.5 mM), add glutathione (final concentration of 5 mg / mL) as a stabilizer, and adjust the solution pH to about 4.5. Reduce Cu ions to form Cu NCs by chemical reduction (such as NaBH4), and the nanoclusters are stably dispersed.
[0035] Step 3: Slowly add 1 mL of Cu NCs dispersion (concentration: 5 mg / mL) to 1 mL of SiNSs suspension (concentration: 10 mg / mL), and ultrasonicate for 1 hour at room temperature to promote the uniform distribution of Cu NCs on the surface of SiNSs; then, continue to stir vigorously for 1 hour to ensure that Cu NCs are fully loaded onto the surface of SiNSs, forming a stable Si@Cu NSs composite material; finally, the obtained product is centrifuged to remove unbound Cu NCs, washed repeatedly with deionized water, and stored at 4 °C for subsequent experiments.
[0036] The prepared multi-mode synergistic antibacterial nanomaterials (Si@Cu NSs composite material) were characterized by transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), atomic force microscopy (AFM), etc. The results are as Figure 1 shown. Among them, Figure 1 a is the transmission electron microscopy image of Si@Cu NSs. Multiple nanosheet structures can be seen, which are silicene nanosheets (Si NSs); the enlarged image in the upper right corner (within the blue dotted line box) shows a more detailed structure, and some granular substances can be seen attached to the silicene nanosheets (Si NSs), which may be Cu NCs. Figure 1 b is the elemental distribution image of Si@Cu NSs, showing the distribution of Cu, Si, and O elements in the material. Figure 1 c is the atomic force microscopy image of Si@Cu NSs. The results show that the Si@Cu NSs were successfully prepared in this invention.
[0037] Example 2
[0038] This example proves that: by utilizing the p-d orbital hybridization effect between SiNSs and Cu NCs, the redox cycle between Cu + / Cu 2+ is promoted, thereby significantly enhancing the catalytic ability and improving the CDT effect.
[0039] (1) Catalytic enhancement mechanism of orbital hybridization effect
[0040] SiNSs have abundant p orbitals, which can hybridize with the d orbitals of Cu NCs, increasing the electron cloud density of Cu and enhancing its adsorption ability for H2O2.
[0041] Using density functional theory (DFT) calculations ( Figure 2 ), analyze the catalytic mechanism of Si@Cu NSs in chemodynamic therapy (CDT), and verify the p-d orbital hybridization effect on Cu + / Cu2+ Enhancement of the redox cycle. The electronic structure calculation of the Si@CuNSs composite shows that as a substrate material, SiNSs can form a strong interaction with CuNCs, causing the hybridization of the d orbitals of Cu and the p orbitals of Si, thereby increasing the electron cloud density of Cu and promoting the + / Cu 2+ redox cycle. Through the Bader charge analysis of Cu in the Si@Cu system, it is found that the charge transfer of Cu atoms increases significantly, indicating that Si provides an additional electron donor and enhances the catalytic activity of Cu.
[0042] (2) Generation of free radicals in the CDT reaction
[0043] The generation of free radicals was determined by electron paramagnetic resonance (EPR), and the improvement of the free radical yield after the loading of CuNCs was verified. The results are as Figure 3 shown. The Si@Cu composite shows enhanced absorption characteristics in the presence of MB, indicating enhanced catalytic decomposition ability towards MB; the Si@Cu composite shows an enhanced EPR signal, indicating a significant increase in the free radical yield after the loading of Cu NCs.
[0044] It can be seen that the orbital hybridization effect can significantly reduce the energy barrier of H2O2 decomposition, increase the yield of free radicals (·OH), and enhance the antibacterial ability of CDT.
[0045] Example 3
[0046] This example verified that Si@CuNSs improved the antibacterial ability by combining photothermal therapy (PTT) and chemodynamic therapy (CDT).
[0047] The antibacterial ability of Si@Cu under PTT+CDT conditions was evaluated by bacterial live / dead staining experiments, and the bacterial survival rate was analyzed by flow cytometry. The photothermal effect of Si@Cu nanomaterials was characterized by infrared thermal imaging (IR) technology, and its photothermal conversion efficiency was measured. The destruction of the bacterial membrane structure was observed by combining TEM to verify the enhanced effect of the synergistic effect.
[0048] The results are as Figure 4 shown. SiNSs have excellent near-infrared absorption ability in the NIR-II region, exhibit efficient photothermal conversion under 1064 nm laser irradiation, increase the local temperature, accelerate the destruction of the bacterial membrane, and enhance the CDT reaction of CuNSs, making the Si@Cu nanomaterials have stronger antibacterial ability.
[0049] Example 4
[0050] To study the in vivo safety of Si@Cu NSs, the main organs of mice were collected and sectioned for HE staining. The results show that (Figure 5 ), no obvious tissue damage or inflammatory changes were observed in all important organs. In summary, Si@CuNSs is an antibacterial nanomaterial with excellent biocompatibility and has potential clinical application value.
[0051] As described above, only the preferred embodiments of the present invention are given, and thus do not limit the implementation manners and protection scope of the present invention. For those skilled in the art, it should be realized that all the equivalent replacements and obvious changes made by using the content of the specification and drawings of the present invention should be included within the protection scope of the present invention.
Claims
1. A multi-mode collaborative antibacterial nanomaterial, characterized in that, It includes two-dimensional silicene nanosheets and copper nanoclusters supported on their surfaces.
2. A preparation method of the multi-mode collaborative antibacterial nanomaterial as described in claim 1, characterized in that, It includes the following steps: Step 1, prepare high-quality two-dimensional silicene nanosheets by wet chemical exfoliation method; Step 2, synthesize CuNCs by chemical reduction method; Step 3, slowly add the Cu NCs dispersion to the two-dimensional silicene nanosheet suspension, and ultrasonicate at room temperature to promote the uniform distribution of CuNCs on the surface of the two-dimensional silicene nanosheets; continue to stir vigorously to ensure that Cu NCs are fully loaded onto the surface of the two-dimensional silicene nanosheets to form a stable Si@Cu NSs composite material; centrifuge to remove unbound Cu NCs, and wash repeatedly with deionized water to obtain the multi-mode synergistic antibacterial nanomaterial.
3. The preparation method according to claim 2, wherein The specific method for preparing high-quality two-dimensional silicene nanosheets by wet chemical exfoliation method is: under an argon protection atmosphere, weigh the CaSi2 precursor and iodine, disperse them in anhydrous acetonitrile at a molar ratio of 1:1, and stir at room temperature for 2-3 weeks to promote the formation of silicene; after the reaction is completed, use centrifugation to remove by-products and wash multiple times to improve the purity of the two-dimensional silicene nanosheets.
4. The preparation method according to claim 2, wherein, The specific method for synthesizing Cu NCs by chemical reduction method is: dissolve CuSO4·5H2O in ultrapure water, add glutathione as a stabilizer, and adjust the solution pH to 4.0-5.0, and reduce Cu ions by chemical reduction to form CuNCs.
5. The preparation method according to claim 4, characterized in that, The concentration of the CuSO4·5H2O is 0.5-0.8 mM; the concentration of the glutathione is 5-7 mg / mL; the reducing agent used is NaBH4.
6. The preparation method according to claim 2, wherein The preparation method of the two-dimensional silicene nanosheet suspension is: redisperse the two-dimensional silicene nanosheets prepared in Step 1 in an N-methylpyrrolidone solution, and ultrasonicate at 900 W for 8-12 hours under ice bath conditions to finally obtain a highly dispersible two-dimensional silicene nanosheet suspension.
7. The preparation method according to claim 2, wherein The concentration of Cu NCs in the CuNCs dispersion is 5-10 mg / mL; the concentration of two-dimensional silicene nanosheets in the two-dimensional silicene nanosheet suspension is 10-15 mg / mL.
8. The preparation method according to claim 2, characterized in that, In Step 3, the ultrasonication time is 1-3 hours, and the vigorous stirring time is 1-3 hours.
9. Use of the multi-mode synergistic antibacterial nanomaterial according to claim 1 in the preparation of anti-bacterial infection drugs.
Citation Information
Cited By
Microneedle patch for closed-loop management of drug-resistant bacteria infected wounds of animals as well as preparation method and application of microneedle patch
CN121868039A